Product Development using SWOT Analysis - Felicia Apsarini Soegoto (Universitas Komputer Indonesia, 2021)
The objective of this research is to give recommendation for a bakery chain operator called Greggs in terms of improving their breakfast menu selection to generate more sales. The research method uses SWOT analysis to produce a strategic development plan. Greggs is one of the largest United Kingdom bakery stores and performs well in generating revenue as the turnover. The uncertainty of Brexit, the minimum wage set by the government, the highest proportion of people who usually eat breakfast on the go, development of a mobile app, breakfast preference to a healthier fresh meal and reduce sugar consumption, competitor, extreme winter weather, and the government policy have an impact on Gregg revenue. Based on the SWOT analysis result it can be concluded that Gregg needs to utilize the position as the market leader to promote the benefit of high-quality healthy food, use the revenue to start on research for healthy products innovation, use the healthy breakfast trend to introduce vegan breakfast menu, add more drink option for the breakfast deal to make it more convenient for people to commute, keep focusing on the quality and taste development with a competitive price, add more menu that correspondent with consumer demand, and try to efficiently spend the revenue based on priority to cut operating cost.